Tannic acid shaped microbiome composition in midguts and rearing microcosms of Aedes triseriatus (Say) - Chen, Shicheng; Cui, Liang; Zuo, Bin; Zhao, Jiangchao; Walker, Edward D. (Frontiers in Microbiology, 2026)
IntroductionTannic acid (TA), a polyphenol derived from plants, often accumulates in water-holding containers where mosquitoes develop. Yet, its effects on mosquito gut microbiota remain poorly understood, representing an important knowledge gap. Because mosquito-associated microbiota are vital for host development, nutrition, and immunity, uncovering how TA shapes these microbial communities may yield new insights into mosquito biology and vector control strategies.MethodsIn this study, we conducted a comparative analysis of bacterial communities in Aedes triseriatus midguts and rearing microcosms with or without TA supplement.ResultsAddition of TA at 0.35 mg/mL caused up to 50% larval Ae. triseriatus mortality, whereas combined supplementation with TA and kanamycin (100 μg/mL) increased mortality to 75% relative to controls. TA treatment significantly reduced microbial Chao 1 richness and Shannon diversity in larval and adult mosquito guts, while water and leaf samples were not affected. Distinct microbial community structures were observed between TA-treated and control groups across larvae, adults, water, and leaf surfaces. Pseudomonadota and Bacteroidota dominated all samples, with TA increasing the relative abundance of Pseudomonadota while decreasing Bacteroidota. Notably, Pseudomonas was enriched in TA-treated water, leaf surfaces, and larval midguts. PICRUSt functional predictions indicated enrichment of carbohydrate and amino acid metabolism and membrane transport pathways under TA exposure, reflecting adaptive microbial responses to TA stress.ConclusionOur findings highlight how TA shapes mosquito microbiota and habitat quality, offering potential avenues to manipulate microbial communities as a biocontrol strategy for mosquito larvae.